Brassica Germplasm Characterization, Breeding and Utilization - Ahmed El-Esawi, Mohamed (IntechOpen, 2018)
The genus Brassica L. of the family Brassicaceae has a vital role in agriculture and human health. The genus comprises several species, including major oilseed and vegetable crops with promising agronomic traits. Brassica secondary products have antibacterial, antioxidant and antiviral effects. Characterization of Brassica is important for providing information on domestication, propagation and breeding programs, as well as conservation of plant genetic resources. This book highlights the current knowledge of the genus Brassica L. in order to understand its biology, diversity, conservation and breeding, as well as to develop disease-resistant and more productive crops. This book will be of interest to many readers, researchers and scientists, who will find this information useful for the advancement of their research towards a better understanding of Brassica breeding programs.